2019
DOI: 10.1111/ases.12733
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic repair of anastomotic leakage after low anterior resection for rectal cancer: A systematic review

Abstract: Introduction Anastomotic leakage (AL) after low anterior resection for rectal cancer is a severe complication. Except for re‐operation, several endoscopic options have been proposed for the minimal invasive treatment of AL, including the endoluminal vacuum devices, tissue sealants and Over‐The‐Scope‐Clip (OTSC) technique. The aim of the present review is to evaluate the effect of alternative treatment options for AL repair, by means of endoscopy. Method A bibliographic search was performed in the international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…Therefore, a safe, effective, and well-validated minimally invasive technique is urgently needed in order to attain the best possible short- and long-term outcomes. Even though data are still scarce, EVT has become the most common endoscopic technique for treatment of colorectal leaks after rectal resection [ 5 ], and currently, commercial systems are distributed in more than 40 countries worldwide [ 5 , 6 ]. Compared to stent application or fibrin glue, EVT appears to be a much more versatile endoscopic technique because it allows for the treatment of defects in almost all extraperitoneal locations, regardless of location or size of the defect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a safe, effective, and well-validated minimally invasive technique is urgently needed in order to attain the best possible short- and long-term outcomes. Even though data are still scarce, EVT has become the most common endoscopic technique for treatment of colorectal leaks after rectal resection [ 5 ], and currently, commercial systems are distributed in more than 40 countries worldwide [ 5 , 6 ]. Compared to stent application or fibrin glue, EVT appears to be a much more versatile endoscopic technique because it allows for the treatment of defects in almost all extraperitoneal locations, regardless of location or size of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Today, EVT is the most commonly used technique for endoscopic treatment of postoperative surgical leaks. Commercial systems for EVT are distributed in more than 40 countries worldwide [5,6]. However, existing evidence on EVT for colorectal defects is still based on a and Other Interventional Techniques An abstract of this study entitled "Endoscopic Vacuum Therapy for Colorectal Defects: 20 Years of Experience for In-and Outpatient Treatment" (# 2020-SF-1157-ACS) was accepted as oral presentation in the Scientific Forum at Clinical Congress 2020 in Chicago, IL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review found more options for endoscopic treatment, but most studies are difficult to compare because of the small sample size and variety in treatments and patients. 35 Endoscopic injection with fibrin glue into the anastomotic cavity can be used to close the defect and is mostly used for closing small leaks (<5 mm) or fistulae. 36,37 It can be utilized as an addition to prior treatment, to close a small remaining defect.…”
Section: Endoscopic Application Of Fibrin Glue and Clipsmentioning
confidence: 99%
“…An anastomotic defect can be overcome by over the scope clipping (OTSC) and standard clips used for regular endoscopy to control bleeding or perforation can be used. 35 OTSC can be used in combination with other techniques (e.g., EVAC treatment) and is mainly suitable for small defects (<15 mm).…”
Section: Endoscopic Application Of Fibrin Glue and Clipsmentioning
confidence: 99%